The microbiota of the mother at birth and its influence on the emerging infant oral microbiota from birth to 1 year of age: a cohort study. Issue 1 (1st January 2019) - Hurley, Eimear; Mullins, David; Barrett, Maurice P.; O'Shea, Carol Anne; Kinirons, Martin; Ryan, C. Anthony; Stanton, Catherine; Whelton, Helen; Harris, Hugh M. B.; O'Toole, Paul W.
ABSTRACT: Background: The acquisition of microbial communities and the influence of delivery mode on the oral microbiota of the newborn infant remains poorly characterised. Methods: A cohort of pregnant women were enrolled in the study ( n = 84). All infants were born full term, by Spontaneous vaginal delivery (SVD) or by Caesarean section (CS). At delivery a saliva sample along with a vaginal/skin sample from the mother. Saliva samples were the taken from the infant within one week of birth, and at week 4, week 8, 6 months and 1 year of age. We used high-throughput sequencing of V4-V5 region 16S rRNA amplicons to compare the microbiota of all samples. Results: The vaginal microbiota had a lower alpha diversity than the skin microbiota of the mother, while the infant oral microbiota diversity remained relatively stable from birth to 8 weeks of age. The oral microbiota of the neonate differed by birth modality up to 1 week of age ( p < 0.05), but birth modality did not have any influence on the infant oral microbiota beyond this age. Conclusions: We conclude thatbirth mode does not have an effect on the infant oral microbiota beyond 4 weeks of age, and the oral microbiota of infants continues to develop until 1 year of age.